MENCEGAH UJARAN KEBENCIAN DALAM KELUARGA (STUDI ANALISIS SIKAP-SIKAP NABI KEPADA ‘AISYAH RADIALLAHU ‘ANHA) - Muhamad Arifin (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
Husband has been settled as a leader in the household according to the guidance of the shariah. One of the main tasks of a husband is to protect his wife and children from things that can harm them, both in this world and the hereafter. One of the things that can harm them is the utterance of hatred which has lately been used very much among the people, especially in various existing information technologies. Technological advances have made human life easier, and usually every increase in speed is followed by heavier risks. Through this research, the writer wants to reveal the tips of the Prophet (Peace be Upon Him) in educating and fortifying his family from bad speech such as utterances which spread hatred in the community. It can cause the background of the occurrence of widow status in women. By knowing these tips, it is hoped that the community can emulate them.